A case series of metastases to the breast from extramammary malignancies - Vaidya, Tanvi; Ramani, Subhash; Rastogi, Ashita (Indian Journal of Radiology and Imaging, 2018)
Metastases to the breast from extra-mammary malignancies are extremely uncommon. The discovery of a breast mass in a patient with a known primary tumor elsewhere poses a diagnostic challenge to the clinician. An awareness of the various malignancies that can metastasize to the breast and accurate diagnosis of the same is essential to avoid an unnecessary mastectomy and to guide further therapy. In this case series, we describe such clinical scenarios with an emphasis on the imaging features of metastases to the breast, which will enable radiologists to recognize this entity with greater ease.
Keywords: Breast; extramammary; mammography; metastases; ultrasound